Golimumab, a human antibody to tumour necrosis factor α given by monthly subcutaneous injections, in active rheumatoid arthritis despite methotrexate therapy: the GO-FORWARD Study. Issue 6 (9th December 2008) - Keystone, E C; Genovese, M C; Klareskog, L; Hsia, E C; Hall, S T; Miranda, P C; Pazdur, J; Bae, S-C; Palmer, W; Zrubek, J; Wiekowski, M; Visvanathan, S; et al.
Abstract : Objective: The phase III GO-FORWARD study examined the efficacy and safety of golimumab in patients with active rheumatoid arthritis (RA) despite methotrexate therapy. Methods: Patients were randomly assigned in a 3 : 3 : 2 : 2 ratio to receive placebo injections plus methotrexate capsules (group 1, n = 133), golimumab 100 mg injections plus placebo capsules (group 2, n = 133), golimumab 50 mg injections plus methotrexate capsules (group 3, n = 89), or golimumab 100 mg injections plus methotrexate capsules (group 4, n = 89). Injections were administered subcutaneously every 4 weeks. The co-primary endpoints were the proportion of patients with 20% or greater improvement in the American College of Rheumatology criteria (ACR20) at week 14 and the change from baseline in the health assessment questionnaire-disability index (HAQ-DI) score at week 24. Results: The proportion of patients who achieved an ACR20 response at week 14 was 33.1% in the placebo plus methotrexate group, 44.4% (p = 0.059) in the golimumab 100 mg plus placebo group, 55.1% (p = 0.001) in the golimumab 50 mg plus methotrexate group and 56.2% (p<0.001) in the golimumab 100 mg plus methotrexate group. At week 24, median improvements from baseline in HAQ-DI scores were 0.13, 0.13 (p = 0.240), 0.38 (p<0.001) and 0.50 (p<0.001), respectively. During the placebo-controlled portion of the study (to week 16), serious adverse events occurred in 2.3%, 3.8%, 5.6% and 9.0% of patients and serious infections occurred in 0.8%, 0.8%, 2.2% and 5.6%, respectively. Conclusion: The addition of golimumab to methotrexate in patients with active RA despite methotrexate therapy significantly reduced the signs and symptoms of RA and improved physical function.